Village Fund Corruption Reflects Weak Integrity of State Apparatus - Cherra Janua Garini; Yogi Prasetyo; Sugeng Wibowo (NOTARIIL Jurnal Kenotariatan, 2026)
This study aims to explore the challenges of transparency in village fund management and corrupt practices in Madiun Regency. Issues discussed include the culture of patronage, regulatory deficiencies, and the low capacity of village officials, all contributing to corruption. The research method employed was qualitative with a descriptive approach, including interviews with stakeholders and document analysis. The study's findings indicate that misuse of village funds has resulted in significant losses to the state and undermined public trust. The cases in Sukosari and Gemarang demonstrate a pattern of systemic corruption through budget inflation and unrealistic procurement. The study's conclusions emphasize the importance of a comprehensive approach to improving oversight, the capacity of village officials, and community involvement in village fund management, in order to create a transparent and accountable village government.